Exequias en Pamplona del magisterio republicano: los orígenes del sistema educativo franquista (II) - López Bausela, José Ramón (Huarte de San Juan. Geografía e Historia, 2007)
In the first part of this article –Huarte de San Juan, nº 13, 2006, pp. 3311-338– we showed that the call of the National Orientation Course in Primary Education was an initiative of a military nature that General Orgaz proposed to Minister Sainz Rodriguez to be co-developed with the aim of moving the raw ideological essence of the spirit behind the military uprising of July 18th, 1936 to the schools. From this perspective we look at the role of the Board of Education of Navarre and its systematic marginalization in the organization of this event developed in Pamplona from 1st to 30th June, 1938. The second part, focusing mainly on curricular issues of the program taught in the course, analyses the division of responsibilities between military and civilian organizers in this matter, showing two key issues. The first, the original proposal of a curriculum “fascistized” led to a sharply fascist one and, second, that the architect of this initiative deposited in his proposal real prospects for the future and continuity.
Keywords: Fascist; fascistized; Formation (Training); Franco’s regime; time table; teachers; Pamplona (Navarre); program; religious sense; military sense